Ambient PM2.5 exposure and sleep quality: Evidence from circadian DNA methylation signatures in a population-based study - Yuting Wang; Shuzhen Liu; Jiahui Rong; Yaxin Luo; Siyuan Niu; Peifeng Guo; Xu Tang; Yujian Liang; Xiaoting Mo; Linhai Zhao; Shiwen Jiang; Tiantian Gu; et al. (Journal of Hazardous Materials, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

First outbreak of trypanosomiasis in farmed blood parrot cichlids (Vieja melanura♀ × Amphilophus citrinellus♂) from southern China - Jun-Yu (俊余) Zhou (周); Liwen (力文) Xu (徐); Ying-Xin (潆心) Bi (毕); Jinyong (晋勇) Zhang (章); Geoff Hide; De-Hua (德华) Lai (赖); Zhao-Rong (照荣) Lun (伦) (Aquaculture, 2024)

Towards disentangling the classification of freshwater fish trypanosomes - Peng Zhang; Jie Liu; Xiao-Ming Yin; Jun-Yu Zhou; Julius Lukeš; Zhao-Rong Lun; De-Hua Lai (Marine Life Science & Technology, 2023)
Currently, new species of freshwater fish trypanosomes, which are economically important parasites, are being described based on subjectively selected features, i.e., their cell morphology and the host species. We have performed detailed phylogenetic and haplotype diversity analyses of all 18S rRNA genes available for freshwater fish trypanosomes, including the newly obtained sequences of Trypanosoma carassii and Trypanosoma danilewskyi . Based on a sequence similarity of 99.5%, we divide these trypanosomes into 15 operational taxonomic units, and propose three nominal scenarios for distinguishing T. carassii and other aquatic trypanosomes. We find evidences for the existence of a low number of freshwater fish trypanosomes, with T. carassii having the widest geographic and host ranges. Our analyses support the existence of an umbrella complex composed of T. carassii and two sister species.

How do precipitation events modify the stable isotope ratios in leaf water at Lhasa on the southern Tibetan Plateau? - Yong Wang; Wusheng Yu; Lun Luo; Minghui Li; Xiaoming Liu; Rong Guo; Yaoming Ma; Baiqing Xu; Guangjan Wu; Chengyi Zhao; Zhaowei Jing; Feili Wei; et al. (Isotopes in Environmental and Health Studies, 2022)

Fertility outcomes in infertile women with complex hyperplasia or complex atypical hyperplasia who received progestin therapy and in vitro fertilization - Miao Li; Jia-lun Song; Ying Zhao; She-ling Wu; Hong-bin Liu; Rong Tang; Lei Yan (Journal of Zhejiang University-SCIENCE B, 2017)

Analysis of genetic diversity in the tuber mustard (Brassica juncea var. tumida Tsen et Lee) in the Yangtze river basin of China - Ping Fang; Fa-Bo Chen; Qi-Lun Yao; Ke-Cheng Yang; Guang-Fan Zhou; Yong-Hong Fan; Zhao-Rong Zhang; Jin-Juan Shen; Hong Zhang (Genetic Resources and Crop Evolution, 2013)

Cathepsin L in the orange-spotted grouper, Epinephelus coioides: molecular cloning and gene expression after a Vibrio anguillarum challenge - Jing-Zhen Liang; Ying-Zhu Rao; Zhao-Rong Lun; Ting-Bao Yang (Fish Physiology and Biochemistry, 2012)

Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.